TRB3 Function in Cardiac Endoplasmic Reticulum Stress - Avery, Joan (2010)
RATIONALE: Tribbles 3 (TRB3) is an intracellular pseudokinase that modulates the activity of several signal transduction cascades. TRB3 has been reported to inhibit the activity of Akt protein kinases. TRB3 gene expression is highly regulated in many cell types, and amino acid starvation, hypoxia, or endoplasmic reticulum (ER) stress promotes TRB3 expression in non-cardiac cells. OBJECTIVE: The objective of this work was to examine TRB3 expression and function in cultured cardiac myocytes and in mouse heart. METHODS AND RESULTS: Agents that induced ER stress increased TRB3 expression in cultured cardiac myocytes while blocking insulin-stimulated Akt activation in these cells. Knockdown of TRB3 in cultured cardiac myocytes reversed the effects of ER stress on insulin signaling. Experimental myocardial infarction led to increased TRB3 expression in murine heart tissue in the infarct border zone suggesting that ER stress may play a role in pathological cardiac remodeling. Transgenic mice with cardiac-specific overexpression of TRB3 were generated and they exhibited normal contractile function but altered cardiac signal transduction and metabolism with reduced cardiac glucose oxidation rates. Transgenic TRB3 mice were also sensitized to infarct expansion and cardiac myocyte apoptosis in the infarct border zone after myocardial infarction. CONCLUSIONS: These results demonstrate that TRB3 induction is a significant aspect of the ER stress response in cardiac myocytes and that TRB3 antagonizes cardiac glucose metabolism and cardiac myocyte survival.